Bio-Inspired Networking - e uthor (London : ISTE Press Ltd. ; Kidlington, Oxford : Elsevier Ltd., 2015)
Bio-inspired techniques are based on principles, or models, of biological systems. In general, natural systems present remarkable capabilities of resilience and adaptability. In this book, we explore how bio-inspired methods can solve different problems linked to computer networks.
Note continued: 3.5.4. The backpropagation algorithm -- 3.6. Applications on networks -- 3.6.1. ANN in intrusion detection systems -- 3.6.2. Fault detection -- 3.6.3. Routing -- 3.7. Further reading -- 3.8. Bibliography -- ch. 4 Swarm Intelligence (SI) -- 4.1. Ant colony optimization -- 4.2. Applications on networks -- 4.2.1. Ants colony on routing -- 4.2.2. Ants colony on intrusion detection -- 4.3. Particle swarm optimization -- 4.4. Applications on networks -- 4.4.1. Particle swarm on node positioning -- 4.4.2. Particle swarm on intrusion detection -- 4.5. Further reading -- 4.6. Bibliography.
Vendor-supplied metadata.
Includes bibliographical references and index.
Keywords: Computer networks; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Computer networks; Electronic books